2020
DOI: 10.3390/su12093615
|View full text |Cite
|
Sign up to set email alerts
|

Design for Sustainability: The Need for a New Agenda

Abstract: Design for Sustainability is not the panacea we hoped it would be when it was first introduced in the latter part of the 20th century. Today, the health of both our environment and our societies is at a critical state, a breaking point, with piecemeal solutions offered as social-media-friendly rallying points, such as the European Parliament approved ban on single-use plastics, whilst fundamental, and arguably less ‘exciting’, issues such as loss of biodiversity, overpopulation, and climate change are shuffled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Design is a profession in which a range of strategies can be intelligently and creatively applied toward the resolution of potentially complex and critical social challenges. [46][47][48] These strategies can vary from digital and/or physical product-level design strategies through to socio-technical, system-level design strategies. Design as a discipline, in this sense, is not the same as design thinking: a simplified business approach for non-designers.…”
Section: A Design-led Approachmentioning
confidence: 99%
“…Design is a profession in which a range of strategies can be intelligently and creatively applied toward the resolution of potentially complex and critical social challenges. [46][47][48] These strategies can vary from digital and/or physical product-level design strategies through to socio-technical, system-level design strategies. Design as a discipline, in this sense, is not the same as design thinking: a simplified business approach for non-designers.…”
Section: A Design-led Approachmentioning
confidence: 99%
“…One reason for the finding that some participants displayed a superficial level of knowledge and understanding may be due to a "combination of misinformation and disinformation" which can lead to the creation of new norms and perceptions resulting in design for unsustainable behavior [60] (p. 5). For example, participant I_17 suggested that they would avoid using recycled aluminum due to its loss of machinable properties.…”
Section: Opportunities To Equip Teachers With Increased Knowledge and Understandingmentioning
confidence: 99%
“…Therefore, the definition of Climate Adaptation Planning (CAP) must take specific local socio-economic contexts into consideration. International scientific communities [26,27,[29][30][31] state that coastal area adaptation should be iterative and dynamic, in recognition of the continuously evolving dynamics present in coastal territorial systems. Furthermore, adaptation measures should consider the local ecology, economy, society, politics and technology [26,[32][33][34][35].…”
Section: Coastal Territories and Climate Change Impactsmentioning
confidence: 99%